1997
DOI: 10.1002/ana.410420106
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile of myelin basic protein—reactive T cells in multiple sclerosis and healthy individuals

Abstract: Myelin basic protein (MBP)-reactive T cells have been implicated in the autoimmune pathogenesis of multiple sclerosis (MS). In this study, we examined the cytokine profile of 531 primary MBP-reactive T-cell lines and 72 independently established clones from 32 patients with MS and 18 healthy controls (NS) by using highly sensitive enzyme-linked immunosorbent assays. An increased number of primary T-cell lines producing interferon-gamma (IFN gamma) and/or interleukin-4 (IL-4) in response to MBP were found in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
44
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 34 publications
2
44
0
1
Order By: Relevance
“…MS patients' autoreactive T cells are generally considered strong secretors of proinflammatory cytokines [36]. Interestingly, our results showed that T cells primed by tolDCs were refractory to further stimulation using myelin peptides-loaded APC, thus emphasizing the tolerogenic potential of tolDCs in MS patients.…”
Section: Discussionmentioning
confidence: 61%
“…MS patients' autoreactive T cells are generally considered strong secretors of proinflammatory cytokines [36]. Interestingly, our results showed that T cells primed by tolDCs were refractory to further stimulation using myelin peptides-loaded APC, thus emphasizing the tolerogenic potential of tolDCs in MS patients.…”
Section: Discussionmentioning
confidence: 61%
“…High levels of TNF-␣ have been identified in MS brain lesions (58), and some reports indicate that levels of Th1 cytokines produced by PBMC (59 -62), by CSF (63), or by myelin-reactive TCC or lines (35,64) have also been associated with disease activity in MS. One analysis of cytokine secretion of 30 MBP-specific TCC revealed elevated IFN-␥:IL-4 ratios in MS patients (65). By contrast, other studies failed to demonstrate clear differences in cytokine profiles of MBP-reactive TCC or T cell lines between patients and controls (66,71).…”
Section: Discussionmentioning
confidence: 99%
“…Agstimulated T cells have the ability to produce TNF-␣ along with IFN-␥ that acts in both innate and specific cell-mediated immunities (2). Activated CD4 ϩ Th1 cells and their secreted cytokines are believed to be crucial to the pathogenesis of multiple sclerosis, especially during the demyelinating episodes (3). The mixture of both TNF-␣ and IFN-␥ may therefore be harmful to neuronal elements.…”
mentioning
confidence: 99%
“…Activation of the inducible form of NO synthase (iNOS) 3 and NO production take place during many neuropathological conditions (7). iNOS is responsible for the cytotoxic action of macrophages and neutrophils and NO has been implicated in neurodegeneration and chronic inflammation (8,9).…”
mentioning
confidence: 99%